Working on my hair: a visual analysis of natural hair and Black women professionals in popular television programming - Blackburn, Hayley Eve, author; Sivakumar, Gayathri, advisor; Martey, Rosa Mikeal, committee member; Gibson, Katie, committee member (Colorado State University. Libraries, 2017)
I examine the representations of Black women characters in professional settings on seven television drama texts. Black features are subjected to Eurocentering—the reduction of racial heritage markers to align with Eurocentric values—to protect hegemonic traditions under the guise of racial neoliberalism. This study focuses on hairstyles for Black women because hair functions as a racial signifier to the audience and is thus a key component of the visual rhetoric under observation. I answer the research question: how does the visibility and representation of natural hair invite the audience to discipline Blackness in professional spaces. The findings reflect that natural hair does lack visibility, with less than 25% of the sample representing significant moments for the main characters to interact with natural hair, and when visible the representation tends towards a disciplinary frame. Natural hair is a symbol of the Black savage framing that reinforces the superiority of Whiteness in the professional world. The Black woman with altered hair becomes a symbol for a civilized, thus successful, Black body able to participate in a professional society while natural hair remains the symbol for the opposite. Overall, audiences are invited to view natural hair in a very limited capacity for professional characters, and the framing reinforces negative perceptions of natural hair for Black women in a work-based Western society.
Zip file contains program tracking spreadsheet.